Sosialisasi dan Edukasi Ketahanan Pangan Berkelanjutan Melalui Pendekatan Fenomenologi Sosial Ekonomi Ibu Rumah Tangga Petani di Desa Pondidaha, Konawe, Sulawesi Tenggara - Mursal Junus (Jurnal Kemitraan Masyarakat, 2025)
Sustainable food security is a strategic issue in rural development that demands a comprehensive approach based on local communities. This community service activity aims to provide socialization and education about sustainable food security through a socio-economic phenomenological approach, focusing on the role of farmer housewives in Pondidaha Village, Konawe Regency. The implementation methods included educational lectures, focus group discussions (FGDs), field visits, and hands-on practice on sustainable food management, involving 20 farmer housewife respondents. The results showed that 80% of participants gained an adequate understanding of the concept of sustainable food security, local food diversification strategies, and an active role in improving family welfare through strengthening socio-economic capacity. The main challenges identified include limited access to resources, the dual role of housewives, and seasonal income instability. The solutions implemented include sustainable agriculture management training, food diversification counseling, and increased local market access. The socio-economic phenomenological approach provides a perspective that the life experiences, cultural values, and habits of farmer housewives are key elements in the success of food security programs at the community level. This activity contributes to increasing public awareness, skills, and participation in realizing sustainable food security, as well as strengthening the role of women in rural development based on local wisdom. This result is expected to be a model of community empowerment that can be replicated in other rural areas with similar characteristics.